Hepatitis E and diaphragmatic dysfunction: Case series and review of the literature - Westhoff, Michael; Arias, Andres; Litterst, Patric (Pneumologie, 2024)
Introduction The causes of diaphragmatic paresis are manifold. An association between neuralgic amyotrophy (NA) and hepatitis E virus (HEV) infection has been reported. We wondered about the prevalence of diaphragmatic disfunction and hepatitis E infection in our clinic. Methods From July 1st, 2020 to August 31st, 2023, patients presenting with diaphragmatic dysfunction and simultaneous clinical symptoms of an acute NA, or a history of NA, as well as patients with previously unexplained diaphragmatic dysfunction were examined for HEV infection. Results By August 31st, 2023, 13 patients with diaphragmatic dysfunction and HEV infection were diagnosed (4 women, 9 men). Mean age was 59 ± 10 years. Liver values were normal in all patients. The median latency to diagnosis was five months (range: 1–48 months); nine patients, 4 of them with typical symptoms of NA, presented with acute onset three patients showed bilateral diaphragmatic dysfunction. All patients had a positive IgG immunoblot. Seven patients, three with NA, had an elevated hepatitis E IgM titer and six of them also a positive IgM immunoblot. In all cases, O2C hepatitis genotype 3 was identified. In eight cases, all those with a high IgG titer >125, the O2 genotype 1 was also detected. Conclusion NA that shows involvement of the phrenic nerve resulting in diaphragmatic dysfunction and dyspnoea, may be associated with HEV infection. The observation of 13 patients with diaphragmatic dysfunctions and HEV infection within a period of three years indicates a high number of undetected HEV-associated diaphragmatic dysfunction in the population, especially in the absence of NA symptoms. Therefore, even in diaphragmatic dysfunction without NA symptoms and causative damaging event, HEV infection should be considered, as it may represent a subform of NA with only phrenic nerve involvement. Therapy of HEV-associated diaphragmatic dysfunction in the acute phase is an open question. In view of the poor prognosis for recovery, antiviral therapy should be discussed. However, no relevant data are currently available.
Keywords: Hepatitis E; neuralgic amyotrphy; diaphragmatic paresis; diaphragmatic dysfunction; phrenic nerve